Performance of stair negotiation in patients with cerebral palsy and stiff knee gait - Lewerenz, Annika; Wolf, Sebastian Immanuel; Dreher, Thomas; Krautwurst, Britta (Gait & posture, 2019)
Background - Due to the limited knee range of motion, achieving adequate foot clearance while walking on level ground constitutes a major problem for patients with cerebral palsy and stiff knee gait. Stair negotiation as an activity of daily life requires a considerably higher knee range of motion than level ground walking, but little is known yet as to whether such patients are able to walk stairs. Research question: The aim of this study was to investigate how patients with a limited knee range of motion negotiate stairs. Do they increase their peak knee flexion and use the same pattern as in walking on level ground? How do the muscles act during stair negotiation? - Methods - In this explorative study, 17 adults with bilateral, spastic cerebral palsy and stiff knee gait and 25 healthy subjects were examined. 3D motion analysis, including electromyography, was performed while walking on level ground, upstairs, and downstairs. A linear mixed model was used for between- and within-group comparisons. - Results - Walking upstairs and downstairs, patients increased their peak knee flexion by around 30° compared to level walking. Thus, increased knee flexion may be seen as the main mechanism for maintaining foot clearance on stairs. An increased pelvic obliquity (elevation) and hip flexion were also found and involved subjects showed a slight increase in rectus femoris activity when walking on stairs compared to level walking within the phases of high knee flexion. - Significance - This study showed that patients with cerebral palsy and stiff knee gait are able to flex their knees more than would be required for level walking. Hence, the patients are able to adapt their rectus activity to stair walking to some extent. Therefore, further investigations might help to open up new therapeutic options to facilitate level walking and stair negotiation in patients with stiff knee gait.